2014
DOI: 10.1007/s00586-014-3185-2
|View full text |Cite
|
Sign up to set email alerts
|

Answer to the Letter to the Editor of Feng Li et al. entitled “Minimally invasive versus open transforaminal lumbar interbody fusion: a meta-analysis based on the current evidence” by Nai-Feng Tian, Yao-Sen Wu, Xiao-Lei Zhang, Hua-Zi Xu, Yong-Long Chi, Fang-Min Mao (2013). Eur Spine J, doi:10.1007/s00586-013-2747-z

Abstract: We thank the readers for their comments on our article entitled ''Minimally invasive versus open transforaminal lumbar interbody fusion: a meta-analysis based on current evidence'' (Eur Spine J 22:1741-1749) [1]. We would like to respond to the comments one by one.1. We searched only the MEDLINE database because most journals on orthopaedics and spinal surgery were included in this database. Searching only in this database might be insufficient. Therefore, we screened the references of the retrieved articles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…For example, one study found an average operating time of 161 minutes for the MIS approach compared to 375 minutes for the open approach [ 16 ]. In contrast, a study in the same meta-analysis found an average operating time of 159.2 minutes for the MIS approach versus 113.06 minutes for the open approach [ 17 ]. We suspect that confounding variables have an important impact on operating time, which would explain the significant variability between studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study found an average operating time of 161 minutes for the MIS approach compared to 375 minutes for the open approach [ 16 ]. In contrast, a study in the same meta-analysis found an average operating time of 159.2 minutes for the MIS approach versus 113.06 minutes for the open approach [ 17 ]. We suspect that confounding variables have an important impact on operating time, which would explain the significant variability between studies.…”
Section: Discussionmentioning
confidence: 99%